ELSA SPEAK APPLICATION TO IMPROVE THE STUDENTS’ PRONUNCIATION AT MEMBER OF LIBAM: (LINTASAN IMAJINASI BAHASA MAHASISWA) - Siti Rahmahyana Rahman; Nurhamdah Nurhamdah; Munawir Munawir (Al-Irsyad: Journal of Education Science, 2024)
The lack of familiarity among students with learning English word pronunciation is a pressing issue that needs immediate attention. Mastering both the meaning and pronunciation of vocabulary is crucial. Many students aspire to speak English with a good accent, and they would greatly benefit from additional resources to practice pronunciation. One such solution is the Elsa Speak Application, which has proven effective in addressing students’ pronunciation difficulties. In this research conducted at LIBAM IAIN Parepare, an experiment design using pre and posttests was implemented with a sample of 15 students selected through cluster random sampling. The results indicated that students’ pronunciation at LIBAM was initially categorized as poor in the pretest (score: 52.00), but significantly improved to a very good category in the posttest (score: 82.00). The indicators focused on vowel and consonant sounds, as well as word and sentence stress. The analysis of the improvement demonstrated that the null hypothesis was rejected (t-value: 2.497 > 1.345), confirming the acceptance of the alternative hypothesis. Therefore, the research concluded that there was a noticeable improvement in students’ pronunciation using the Elsa Speak Application at LIBAM IAIN Parepare.